2021
DOI: 10.3390/ijms22126266
|View full text |Cite
|
Sign up to set email alerts
|

Active Surveillance in Prostate Cancer: Role of Available Biomarkers in Daily Practice

Abstract: Prostate cancer (PCa) is the most commonly diagnosed cancer in men. The diagnosis is currently based on PSA levels, which are associated with overdiagnosis and overtreatment. Moreover, most PCas are localized tumours; hence, many patients with low-/very low-risk PCa could benefit from active surveillance (AS) programs instead of more aggressive, active treatments. Heterogeneity within inclusion criteria and follow-up strategies are the main controversial issues that AS presently faces. Many biomarkers are curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Accordingly, PHI appeared in the diagnostic algorithm for patients with suspected PCa both to select patients for MRI and biopsy [ 35 ]. In addition, PHI has been proposed as a tool to select and monitor patients on active surveillance (AS) [ 36 , 37 , 38 ], and the diagnostic accuracy of PHI for the identification of csPCa might be increased when combined with mpMRI. Several authors showed that the addition of PHI and PHI density to a multivariable model including PI-RADS v2 was able to predict biopsy reclassification with AUCs higher than 0.80 [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, PHI appeared in the diagnostic algorithm for patients with suspected PCa both to select patients for MRI and biopsy [ 35 ]. In addition, PHI has been proposed as a tool to select and monitor patients on active surveillance (AS) [ 36 , 37 , 38 ], and the diagnostic accuracy of PHI for the identification of csPCa might be increased when combined with mpMRI. Several authors showed that the addition of PHI and PHI density to a multivariable model including PI-RADS v2 was able to predict biopsy reclassification with AUCs higher than 0.80 [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…PROGENSA PCA3 is the first FDA-approved urine-based molecular test that detects the overexpression of the PCA3 gene [66]. In conjunction with clinical information, this test could help in the decision to repeat a biopsy.…”
Section: Urine Biomarkersmentioning
confidence: 99%
“…Active surveillance is accepted as a management option for favorable-risk prostate cancer. However, due to the heterogeneity of this population, the lack of personalized risk assessments and the absence of treatment, the long-term outcome of active surveillance is not satisfying for approximately 30% of patients ( Dhawan et al, 2016 ; Moschini et al, 2017 ; Overland et al, 2019 ; Pastor-Navarro et al, 2021 ). Since active surveillance patients are diagnosed with either prostatic intraepithelial neoplasia (PIN) or early-stage cancer (Gleason <6), it is apparent that various carcinogenic signaling pathways are already activated and can lead to pathological or clinical progression.…”
Section: Introductionmentioning
confidence: 99%